Study on Influence of Heavy Oil Reservoir Damage Caused by Multi-Component Thermal Fluid Huff and Puff - Yu, Xinan; Liu, Xilei; Chen, Mingming; Wu, Guanghuan; Li, Xiaoping (Frontiers in Energy Research, 2022)
Multi-component thermal fluid (MCTF) huff and puff technology is an innovative heavy oil development technology widely used in China offshore oilfields. MCTFs mainly include steam, N2 and CO2. Under high temperature and high pressure, the physical and chemical reactions between thermal fluids and rocks occur, damaging the reservoir permeability and production effect. In this paper, 16 groups of core comparison experiments were carried out by MCTF device, the influence of original permeability, temperature and component on reservoir damage was quantitatively studied, and a mathematical model was established. Finally, the influence of reservoir damage on heavy oil development was investigated through numerical simulation. The experimental study reveals that MCTF has an obvious damage effect on the reservoir, where temperature and PV dominate the damage degree; with the increase of MCTF injection volume(PV), the core permeability rapidly decreases initially and stabilizes later (>6PV). The numerical simulation results show that reservoir damage could lead to a recovery drop by 6.9% during MCTF development; on the premise of considering reservoir damage, MCTF huff and puff will further improve oil recovery by 9.68% compared with pure steam. The research is of great significance for understanding the production law of MCTF huff and puff and helpful for promoting the development of offshore heavy oil reservoir.